The Concomitance of Cervical Spondylosis and Adult Thoracolumbar Spinal Deformity - Weber, Michael H.; Hong, C. H.; Schairer, William W.; Takemoto, Steven; Hu, Serena S. (Evidence-Based Spine-Care Journal, 2014)
Study Design Retrospective cross-sectional study.Clinical Question What is the prevalence of cervical spondylosis (CS) and thoracolumbar (TL) spinal deformity in an administrative database during a 4-year study period? Is the prevalence of CS or TL deformity higher in patients who have the other spine diagnosis compared with the overall study population? Are patients with both diagnoses more likely to have undergone spine surgery?Patients and Methods An administrative claims database containing 53 million patients with either Medicare (2005–2008) or private payer (2007–2010) insurance was used to identify patients with diagnoses of CS and/or TL deformity. Disease prevalence between groups was compared using a χ2 test and reported using prevalence ratios (PR).Results The prevalence of CS was higher in patients with TL deformity than without TL deformity, for both Medicare (PR = 2.81) and private payer (PR = 1.79). Similarly, the prevalence of TL deformity was higher in patients with CS than without CS for both Medicare (PR = 3.19) and private payer (PR = 2.05). Patients with both diagnoses were more likely to have undergone both cervical (Medicare, PR = 1.44; private payer, PR = 2.03) and TL (Medicare, PR = 1.68; private payer, PR = 1.74) spine fusion. All comparisons were significant with p < 0.0001.Conclusions Patients with either CS or TL deformity had a higher prevalence of the other spinal diagnosis compared with the overall disease prevalence in the study population. Patients with both diagnoses had a higher prevalence of having spine surgery compared with patients with only one diagnosis. More studies to identify a causal mechanism for this relationship are warranted.
Keywords: cervical spondylosis; scoliosis; myelopathy; adult spine deformity; administrative claims data